A Study on Maternal Weight Gain and its Correlation with Birth Weight of Baby at Term (Anwer Khan Modern Medical College Journal, 2018)
Background: Maternal weight gain is influenced by several trends in perinatal health that are of great public health concern. Maternal weight gain during the 2nd and 3rd trimesters is an important determinant of fetal growthObjective: To determine the relationship between maternal weight gain and birth weight of baby at term.Methodology : A cross sectional observational study was carried among 50 pregnant women at term were admitted in the Department of Obstetrics and Gynaecology, Shaheed Suhrawardy Medical College and Hospital and Anwer Khan Modern Medical College hospital during the period of January 2014 to July 2014. Data were collected pre-designed data collection sheet.Results: This study found maximum (36%) were age group 21-25 years followed by 28% were 20 years, 24% were 26-30 years, 8% were 31-35 years and only 4% were 36-40 years. The average age was 25 years. Among these 50 pregnant women, 2 cases (4%) had BMI